EVALUATION OF ENVIRONMENTAL AND PHYSIOLOGICAL VARIABLES OF HY-LINE BROWN POULTRY WITH AND WITHOUT ENVIRONMENTAL ENRICHMENT - Ribeiro, A. P.; Silva, L. F.; Menegali, I.; Ferreira, F. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The objective was to verify the influence of treatments with and without environmental enrichment on the behavior of layers and egg quality, as well as to study the thermal variables temperature and humidity during the times when the interaction behavior of birds with enrichment was evaluated employee. Also evaluating the thermal variables of air temperature and relative humidity. The experiment was conducted in a randomized complete block design (DBC) with two treatments (conventional enrichment cages and conventional cages without enrichment) and 18 replicates per treatment, two birds per replicate, for 28 days. The data collected in the experiment were analyzed using a statistical and genetic analysis program (SAEG, 2009), using analysis of variance and subjected to Fisher test at 5% probability to detect the significant difference between treatments evaluated for variables environmental and physiological parameters. To analyze the behavior of the birds, the data were analyzed by means of the χ² Test. According to the temperatures measured in the sensors, there was an evident difference between the times of data collection. There was no significant effect of treatments on egg weight characteristics, albumen height, yolk index, shell thickness, and Haugh Unit. No effect of the lateral blocks on the rectal temperature was observed, but there was a significant effect for blocks on the variables mean of skin temperature and mean body temperature.